Integrated Dissection of lncRNA-miRNA-mRNA Pairs and Potential Regulatory Role of lncRNA PCAT19 in Lung Adenocarcinoma - Tang, Xiaomei; Hua, Xiaoyan; Peng, Xujin; Pei, Yongyan; Chen, Zhigang (Frontiers in Genetics, 2022)
Lung adenocarcinoma (LUAD) is the main cause of cancer‐related deaths worldwide. Long noncoding RNAs have been reported to play an important role in various cancers due to their special functions. Therefore, identifying the lncRNAs involved in LUAD tumorigenesis and development can help us improve therapeutic strategies. The TCGA-LUAD RNA expression profile was downloaded from TCGA, and a total of 49 differential lncRNAs, 112 differential miRNAs and 2953 differential mRNAs were screened. Through Kaplan-Meier curves, interaction networks, hub RNAs (lncRNAs, miRNAs, mRNAs) were obtained. These hub genes are mainly involved in cell proliferation, the cell cycle, lung development and tumor-related signaling pathways. Two lncRNAs (SMIM25 and PCAT19) that were more related to the prognosis of lung adenocarcinoma were screened out by univariate Cox analysis, multivariate Cox analysis and risk model analysis. The qPCR results showed that the expression levels of SMIM25 and PCAT19 were down-regulated in clinical tissues, A549 and SPC-A1 cells, which was consistent with the bioinformatics analysis results. Subsequently, the PCAT19/miR-143-3p pairs were screened through WGCNA and miRNA-lncRNA regulatory network. Dual-luciferase detection confirmed that miR-143-3p directly targets PCAT19, and qPCR results indicated that the expression of the two is positively correlated. Cell function tests showed that overexpression of PCAT19 could significantly inhibit the proliferation, migration and invasion of A549 and SPC-A1 cells. In contrast, knockout of PCAT19 can better promote the proliferation and migration of A549 and SPC-A1 cells. The expression of PCAT19 was negatively correlated with tumor grade, histological grade and tumor mutation load in lung adenocarcinoma. In addition, co-transfection experiment confirmed that the miR-143-3p mimic could partially reverse the effect of PCAT19 knockout on the proliferation of A549 and SPC-A1 cells. In summary, PCAT19 is an independent prognostic factor in patients with lung adenocarcinoma that can regulate the proliferation, migration and invasion of lung adenocarcinoma cells, and may be a potential biomarker for the diagnosis of lung adenocarcinoma. PCAT19/miR-143-3p plays a very important regulatory role in the occurrence and development of lung adenocarcinoma.